1998
DOI: 10.1016/s0029-7844(98)00247-6
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence screening practices of obstetrician-gynecologists

Abstract: Routine screening of all women for domestic violence has been recommended by ACOG for more than a decade. The majority of obstetrician-gynecologists screen both pregnant and nonpregnant patients when they suspect abuse. However, with universal screening, more female victims of violence can be identified and can receive needed services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The Intimate Partner Abuse Questionnaire (IPAQ) used within the study was developed by the authors after a review of the relevant literature (Faramarzi et al 2005;Ghazizadeh 2005;Horn 1998;Vakili et al 2010). Specifically, the Abuse Assessment Screening (Horn 1998) provided the basis for the IPAQ; culturally-sensitive items related to different types of violence were added, and those which were deemed unsuitable were deleted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Intimate Partner Abuse Questionnaire (IPAQ) used within the study was developed by the authors after a review of the relevant literature (Faramarzi et al 2005;Ghazizadeh 2005;Horn 1998;Vakili et al 2010). Specifically, the Abuse Assessment Screening (Horn 1998) provided the basis for the IPAQ; culturally-sensitive items related to different types of violence were added, and those which were deemed unsuitable were deleted.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the Abuse Assessment Screening (Horn 1998) provided the basis for the IPAQ; culturally-sensitive items related to different types of violence were added, and those which were deemed unsuitable were deleted. The IPAQ was very similar to the instrument used by Faramarzi et al (2005) and Ghazizadeh (2005).…”
Section: Methodsmentioning
confidence: 99%
“…However, this method results in the lowest screening rates with only 8% to 45% of women in the emergency room and 10% to 42% in office-based settings screened according to ACOG guidelines, with more than 50% of providers not screening at all for IPV and one third screening only if a patient presents with a bruise or laceration; younger women, who are at greatest risk for IPV and subsequent injury, are screened the least [10,21,112,[118][119][120][121][122]. The low screening rates for IPV imply that significant barriers for health care professionals impede routine screening.…”
Section: Barriers To Screeningmentioning
confidence: 99%
“…To raise the comfort level of medical staff and improve screening rates, educational programs are available that incorporate specific training and tools for response [14,98,[118][119][120][121]123,124]. When a woman screens positive for IPV, the provider, after acknowledging the positive response, should asked directly how he or she can help.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…10 Although most obstetrician-gynecologists appear to be familiar with the nature and consequences of intimate partner violence, they routinely screen for intimate partner violence only 20% of the time, an estimate that, although low, exceeds that of health care providers in other specialties. [11][12][13] Prior research has shown that obstetrician-gynecologists may selectively screen patients for intimate partner violence based on certain patient characteristics. In one survey of 962 practicing obstetriciangynecologists in the United States, 46% indicated that the type of patient influenced their decision to ask about partner abuse.…”
mentioning
confidence: 99%